Efektivitas Implementasi Kebijakan Penanganan Kemiskinan Perkotaan Di Kecamatan Nusaniwe Kota Ambon - Hamin, Kamsal; Ohoiwutun, St.K.; Selanno, Hendry (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
This study aims to analyze (1) the implementation of policies for handling urban poverty in Nusaniwe District, Ambon City, (2) the effectiveness of implementing policies for handling urban poverty in Nusaniwe District, Ambon City, (3) factors that influence the implementation of policies for handling urban poverty in Nusaniwe District, Ambon City and (4) strategies for handling urban poverty in Nusaniwe District, Ambon City. Data were analyzed using qualitative analysis. The results of the study concluded that (1) Poverty management policies in Ambon City have been elaborated through various work programs and are made based on the needs of target households and their implementation is in accordance with the main tasks and functions of the related regional apparatus organizations; (2) Policy implementation for handling poverty has not been maximized in terms of policy accuracy, implementation accuracy, target accuracy, environmental accuracy and process accuracy; (3) Factors that influence the implementation of policies for handling urban poverty are policy errors, distribution of social assistance and weak data accuracy and (4) Strategies for handling urban poverty in Ambon City are focused on political will and institutional dimensions, both dimensions of policy content and third dimensions of the policy environment .